2006
DOI: 10.1080/02786820600728668
|View full text |Cite
|
Sign up to set email alerts
|

Dominant Mechanisms that Shape the Airborne Particle Size and Composition Distribution in Central California

Abstract: The size and composition of ambient airborne particulate matter is reported for winter conditions at five locations in (or near) the San Joaquin Valley in central California. Two distinct types of airborne particles were identified based on diurnal patterns and size distribution similarity: hygroscopic sulfate/ammonium/nitrate particles and less hygroscopic particles composed of mostly organic carbon with smaller amounts of elemental carbon. Daytime PM 10 concentrations for sulfate/ammonium/nitrate particles w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 33 publications
4
66
1
Order By: Relevance
“…Coastal sites typically experience high concentrations of Na + and Cl − in the coarse-particle diameter range (Nolte et al 2008). Although the MOUDI observations at the coastal Bodega Bay site only covered fine-diameter particles (D aero < 1.8 µm), results in Figure 3 of Herner et al (2006) suggest that coarse Na + and Cl − were substantially under-predicted here. This underprediction is primarily due to the lack of enhanced sea-salt emissions from the coastal surf zone in CMAQv4.6.…”
Section: Particle Mass Size Distributionsmentioning
confidence: 48%
See 2 more Smart Citations
“…Coastal sites typically experience high concentrations of Na + and Cl − in the coarse-particle diameter range (Nolte et al 2008). Although the MOUDI observations at the coastal Bodega Bay site only covered fine-diameter particles (D aero < 1.8 µm), results in Figure 3 of Herner et al (2006) suggest that coarse Na + and Cl − were substantially under-predicted here. This underprediction is primarily due to the lack of enhanced sea-salt emissions from the coastal surf zone in CMAQv4.6.…”
Section: Particle Mass Size Distributionsmentioning
confidence: 48%
“…Values for simulation parameters (e.g., breathing frequency, tidal volume) were chosen to match those of Asgharian et al (2001), except that oral rather than endo-tracheal breathing is simulated here. Also, particle density was set to 1.3 g cm -3 to approximate wood smoke particles (Herner et al 2006), although increasing the density to 1.8 g cm -3 had little impact on results.…”
Section: Lung Deposition Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…3, the indoor behavior of BC aerosol is governed by physical penetration and deposition losses only. The measurements performed in Bakersfield (Herner et al, 2006) showed that both BC and OC fall in the same size range in the wintertime; thus if both species are governed by the same physical loss factors, both should have similar indoor/outdoor ratios. During other seasons, BC and OC may be present in different size ranges, which would alter the physical factors controlling the indoor-outdoor ratio.…”
Section: Indoor Outdoor Carbon Behaviormentioning
confidence: 99%
“…It is necessary, therefore, to have some knowledge of the size resolved chemical composition of the aerosol in the Fresno area. Few such measurements exist; however, data of this type was collected in Bakersfield as part of the California Regional Particulate Air Quality Study conducted at the same time as the present study (Herner et al, 2006). Bakersfield is 124 miles southeast of Fresno, and experiences similar meteorology and air quality issues.…”
Section: Indoor Outdoor Carbon Behaviormentioning
confidence: 99%